RESPON TANAMAN CABAI MERAH (Capsicum annum L.) YANG DIAPLIKASIKAN BAKTERI ENDOFITIK DIAZOTROF DAN PUPUK N TERHADAP POPULASI ENDOFITIK DIAZOTROF, KONSENTRASI N, DAN BOBOT KERING TANAMAN PADA INCEPTISOLS JATINANGOR - Mieke Rochimi Setiawati; Pujawati Suryatmana; Emma Trinurani Sofyan (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2018)
The aim of the research was to determine the effect of nitrogen-fixing endophytic bacteria and N fertilizer on population of nitrogen-fixing (diazotroph) endophytic bacteria, N concentration and dry matter of red chili plant (Capsicum annuum L.) on Inceptisols from Jatinangor. The experiment conducted design was Randomized Block Design in factorial pattern consisted of two factor and three replication. The first factor was diazotroph endophytic bacteriaconsisted two levels: without used diazotroph endophytic bacteria, and used diazotroph endophytic bacteria. The second factor was dosage of N anorganic fertilizer consisted four levels 0, 50, 100 and 150 kg N ha-1. The results showed that there is interaction found between diazotroph endophytic bacteria and N inorganic fertilizer on population of diazotroph endhophytic bacteria but there were not interaction effect on N concentration and dry matter of red chili plant. Independenly, treatment giving diazotroph endophytic bacteria and N anorganic fertilizer showed not significant effect on N concentration of plant. While the treatment of diazotroph endophytic bacteria and 150 kg N ha-1 inorganic fertilizer were independenly each could significantly increased dry matter of red chili plant on Inceptisols from Jatinangor. Keywords: Diazotroph endophytic bacteria, N fertilizer, Red chili plant